Inclusion of rehabilitation medicine concepts in school of medicine resources. (August 2014) - Graham, Susan; Eley, Diann; Cameron, Ian; Thistlethwaite, Jill
Abstract Purpose: To perform a gap analysis of rehabilitation medicine learning objectives (RMLOs) coverage within school of medicine (SOM) curriculum and educational resources as a basis for development of educational resources to fill any identified gaps. Method: Following ethics approval, interviews were carried out with SOM academics and clinicians to assess the relevance of a set of RMLOs and the extent to which RMLOs were addressed in SOM resources. Interviewee opinion was quantified via Likert scales and additional free comments were subjected to thematic analysis. Results: Most RMLOs were perceived as relevant by more than half of the 18 participants. There was evidence of relevant material relating to each RMLO in SOM resources. Thematic analysis suggested that rehabilitation medicine was addressed at the SOM in less detail than outlined in the RMLOs, and that additional rehabilitation content could be included in SOM resources across a number of courses and year levels. Conclusions: Rehabilitation medicine is considered relevant by clinicians and academics at the SOM. The most effective way of filling identified gaps in coverage of rehabilitation medicine at the SOM will be via engagement across a number of medical and surgical disciplines. Implications for Rehabilitation Rehabilitation-related knowledge and skills are relevant to medical education. Many of these issues are already partially addressed in existing educational resources. The design and delivery of medical school curricula should include a trans-disciplinary and inter-year approach to the inclusion of rehabilitation concepts and aptitudes. This could be done by introducing relevant concepts early, making resources available online, and embedding rehabilitation items across different disciplines, courses and assessments.